Pengefisiensian Penyaluran Barang dan Rute Pengiriman Ekspedisi JNE dengan Aplikasi Graf - S, Richasanty Septima; Zulfa, Ira (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Nowadays, online shopping trend is very popular and it is common in the era of advanced technology like now. This affects large companies in Indonesia to provide good, effective and efficient shipping services for customer satisfaction. Each delivery service has its own stages of distribution of goods in the process of sending goods from the sender's hand to the recipient's hand. In addition to the stages of distribution of goods, there are other things that must be considered by shipping service providers, namely effective and timely delivery routes. Graph is a science that can be implemented in the stages of distribution of goods and efficiency of delivery routes. The approach used in making freight routes is the Hamilton trajectory with a circular model.